PRACTICE OF SMALL AND MEDIUM-SIZED ENTERPRISE PERFORMANCE EVALUATION IN LATVIA - Kotane, Inta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The total number of small and medium-sized enterprises signifies an essential share of the national economy; SMEs’ importance is evaluated by the value added and the new jobs created. Despite the growing research interest in the small and medium business performance measurement, there is no consistent opinion among researchers regarding small and medium business performance indicators, their measurement, and methods of assessment. The research study is based on an analysis of literature and scientific publications, the assessment of the financial indicators used by the Latvian institutions for the company’s financial analysis, and an expert survey. The general scientific research methods are used in the research study: information analysis and synthesis, logical construction, monographic, an expert survey, data grouping, and the graphical method. The aim of the research – to carry out an analysis of the performance evaluation practice for small and medium-sized enterprises in Latvia. A study of the small and medium sized business performance measurement and management is carried out and the analysis of the financial indicators used for the performance measurement of small and medium-sized enterprises is performed in the result.